72.4k views
5 votes
Solve the inequality/Solve for X:

((5x+3)(3x-2))/((x^3-7)^2) \geq 0

User Gaohomway
by
6.3k points

1 Answer

5 votes

If
x is real, then
(x^3-7)^2 will always be non-negative, so the sign of the numerator will determine the solution to the inequality. In order for the expression on the left hand side to be defined, we require


(x^3-7)^2\\eq0\implies x^3\\eq7\implies x\\eq\sqrt[3]7\approx1.91

We have


(5x+3)(3x-2)=0\implies x=-\frac35=-0.6,x=\frac23\approx0.66

so there are three intervals we need to check.

(1) We pick a value of
x from
-\infty<x<-\frac35, say
x=-1. This gives the numerator a value of
(-5+3)(-3-2)=(-2)(-5)=10>0.

(2) From
-\frac35<x<\frac23, we can pick
x=0 and we get
(0+3)(0-2)=-6<0.

(3) From
\frac23<x<\infty, we can pick
x=1 and get
(5+3)(3-2)=8>0. But remember, we can't let
x=\sqrt[3]7.

So the solution to the inequality is the union of the two intervals that we showed would make the numerator positive, while still avoiding making the expression undefined:


\left(-\infty,-\frac35\right]\cup\left(\frac23,\sqrt[3]7\right)\cup\left(\sqrt[3]7,\infty\right)

User Dng
by
5.8k points